Breeding of Michaelus phoenissa (Lepidoptera : Lycaenidae) on Senna alata (Fabaceae) in Peru - Faynel, Christophe (2019)
In Villa Carmen, a scientific station near Pillcopata, Cusco, Peru (S 12°53.687' - W 71°24.232', 533 m), we found caterpillars of Michaelus phoenissa (Hewitson, 1867) (Lycaenidae) consuming flowers of Senna alata (L.) Roxb. (Fabaceae). The caterpillars were mostly last instars (between 1 and 1.5 cm in length). They were not visible at first sight because they lodged in unopened flowers. We reared two female and two male adults. None of the immature stages was parasitized. We compare the food plants of M. phoenissa with those of others species of Michaelus Nicolay, 1979.